FORMATION OF ENTREPRENEURSHIP MOTIVATION THROUGH DEVELOPMENT OF LABOR EDUCATION IN SCHOOL AND FAMILY - Jurayeva Nargiza Zokir kizi (Scholar Express Journal, 2022)
This article fully describes the role of social pedagogical institutions such as kindergartens and schools in the development of entrepreneurial motivation through the development of labor education in schools and families, the formation of entrepreneurial motivation through the development of labor education
Keywords: Entrepreneurship; Motivation; Labor Education; Vocational Guidance